Development of essential oils inclusion complexes: a nanotechnology approach with enhanced thermal and light stability - Procopio, Fernanda Ramalho; Brexó, Ramon Peres; Vitolano, Luis Eduardo Sousa; Martins, Maria Eduarda da Mata [UNESP]; Astolfo, Maria Eduarda de Almeida; Bogusz Junior, Stanislau; Ferreira, Marcos David (Springer Nature, 2024)
Essential oils (EOs) are volatile compounds that may have antimicrobial and antioxidant properties. Despite their potential application, low water solubility and chemical instability are limiting factors. Nanoencapsulation processes can overcome this problem, protecting against external factors and promoting a moderate release. Therefore, the objective of the present study was to encapsulate Cymbopogon citratus (CC) and Origanum vulgare (OV) essential oils in β-cyclodextrin (βCD) complexes. Different ratios (w/w) between βCD and EOs (96:4, 92:8, 90:10, 88:12) were tested, seeking greater entrapment efficiency. The particles were characterized by yield, entrapment efficiency, size distribution, morphology, crystallinity, infrared spectroscopy, and thermal behavior. Furthermore, the thermal (70 °C) and photochemical (UV) stability of the free and encapsulated EO was evaluated for 48 h. The results showed that the βCD-CC 90:10 and βCD-OV 90:10 formulations presented greater entrapment efficiency. Crystalline structures of varying sizes (200 to 800 nm), trapezoidal shape, and tendency to aggregation were obtained. Changes in the βCD crystalline organization and the suppression of characteristic free oil absorption bands suggest the EO entrapment. Regarding stability results, βCD-CC remained constant when CC showed losses of 20% (photodegradation) and 60% (thermal degradation) after 48 h of stress exposure. Free OV showed slight variations in absorbance over time, while βCD-OV remained constant over 24 h (thermal degradation) and maintained 60% of oil over 48 h of photo exposure. Furthermore, OV and CC demonstrate color change over time, while βCD-OV and βCD-CC remained constant. The results demonstrate that nanoencapsulation can be an interesting tool for protecting EOs.
Keywords: Inclusion complexes; Thermal analysis; bioactivity